2021
DOI: 10.1101/2021.01.24.21250384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of The Relationship of REMS and MEWS Scores with Prognosis in Patients Diagnosed with Covid-19 Admitted to the Emergency Department

Abstract: AimWith the rapid and global increase in COVID-19 cases, it is becoming important to identify patients with a risk of mortality and patients that need hospitalization. The aim of this study is to try to predict the mortality rate of COVID patients admitted to the emergency department with rapid scoring systems such as REMS and MEWS and their clinical termination in the emergency department at the end of the first month.MethodWe have designed this study to be a single-centered, prospective and an observational … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…In another study, the REMS and MEWS scores were compared. The results confirmed that the REMS (AUC = 0.818, cutoff value of 5 and greater) and MEWS (AUC = 0.681, cutoff value of 3 and greater) scoring systems helped predicting the 1-month mortality of COVID-19 patients (Bas et al, 2022). A retrospective study with 13,830 COVID-19 patients confirmed that the REMS score was a robust tool for predicting ED mortality, hospital mortality, and ED discharge (Bourn et al, 2021).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In another study, the REMS and MEWS scores were compared. The results confirmed that the REMS (AUC = 0.818, cutoff value of 5 and greater) and MEWS (AUC = 0.681, cutoff value of 3 and greater) scoring systems helped predicting the 1-month mortality of COVID-19 patients (Bas et al, 2022). A retrospective study with 13,830 COVID-19 patients confirmed that the REMS score was a robust tool for predicting ED mortality, hospital mortality, and ED discharge (Bourn et al, 2021).…”
Section: Discussionsupporting
confidence: 65%
“…Studies have shown that there is a significant relationship among predisposing factors such as age, gender, and comorbidities, and the clinical course of COVID-19 patients (Bajema et al, 2020; Chan et al, 2020; Chen et al, 2020; Sakurai et al, 2020). These factors are the principal variables for the calculation of physiological scoring systems (Bas, Senturk, Burnaz, Timur, & Kalkan, 2022; Covino et al, 2020).…”
mentioning
confidence: 99%
“…[20] A study including 392 COVID-19 patients admitted to the ED was examined and it was reported that REMS could be guiding for physicians to estimate the one-month mortality of ED patients with COVID-19. [21] In another study, Hai Hu et al…”
Section: Discussionmentioning
confidence: 95%
“…In predicting serious illness development, REMS took second place. The study performed on 392 patients admitted to the emergency department in a hospital in Turkey displayed REMS as a useful scoring system in predicting 1-month mortality and clinical outcome [ 42 ]. A study from the USA on trauma population and another study in the UK in the emergency department showed REMS performed better as a predictor of mortality in emergency medical admissions than other scores [ 31 , 43 ].…”
Section: Discussionmentioning
confidence: 99%